I Want to but I Won't: Pluralistic Ignorance Inhibits Intentions to Take Paternity Leave in Japan - Miyajima, Takeru; Yamaguchi, Hiroyuki (Frontiers in Psychology, 2017)
The number of male employees who take paternity leave in Japan has been low in past decades. However, the majority of male employees actually wish to take paternity leave if they were to have a child. Previous studies have demonstrated that the organizational climate in workplaces is the major determinant of male employees' use of family-friendly policies, because males are often stigmatized and fear receiving negative evaluation from others. While such normative pressure might be derived from prevailing social practices relevant to people's expectation of social roles (e.g., “Men make houses, women make homes”), these social practices are often perpetuated even after the majority of group members have ceased to support them. The perpetuation of this unpopular norm could be caused by the social psychological phenomenon of pluralistic ignorance. While researches have explored people's beliefs about gender roles from various perspectives, profound understanding of these beliefs regarding gender role norms, and the accuracy of others' beliefs remains to be attained. The current research examined the association between pluralistic ignorance and the perpetually low rates of taking paternity leave in Japan. Specifically, Study 1 (n = 299) examined Japanese male employees' (ages ranging from the 20 s to the 40 s) attitudes toward paternity leave and to estimate attitudes of other men of the same age, as well as behavioral intentions (i.e., desire and willingness) to take paternity leave if they had a child in the future. The results demonstrated that male employees overestimated other men's negative attitudes toward paternity leave. Moreover, those who had positive attitudes toward taking leave and attributed negative attitudes to others were less willing to take paternity leave than were those who had positive attitudes and believed others shared those attitudes, although there was no significant difference between their desires to take paternity leave. Study 2 (n = 425) replicated these results and further indicated that they could not be explained by the participants' needs to be socially desirable. Together, our findings suggest that pluralistic ignorance occurs in the context of taking paternity leave in Japanese men, and this leads to the low use of available paternity leave.